Videodermatoscopy of pearly penile papules. Case reports - Hristo Petrov Dobrev; Desislava Georgieva Nocheva (Our Dermatology Online, 2015)
Pearly penile papules are harmless dermatological condition characterized by small dome-shaped to filiform skin-colored papules located in one to several rows along the sulcus or corona of the glans penis. We describe six male patients with pearly penile papules whose diagnosis was assisted by means of videodermatoscopy. All lesions showed a characteristic whitish pink cobblestone appearance arranged in one or several rows. Each papule contained central dotted or commalike vessels and was surrounded by crescent-shaped whitish structures. Videodermatoscopy may assist the diagnosis of pearly penile papules and successfully differentiate them from genital warts and molluscum contagiosum.